Estimating the potential contribution of stroke treatments and preventative policies to reduce the stroke and ischemic heart disease mortality in Turkey up to 2032: a modelling study. (December 2015) - Islek, Duygu; Sozmen, Kaan; Unal, Belgin; Guzman-Castillo, Maria; Vaartjes, Ilonca; Critchley, Julia; Capewell, Simon; O'Flaherty, Martin
Abstract Background Stroke and Ischemic Heart Diseases (IHD) are the main cause of premature deaths globally, including Turkey. There is substantial potential to reduce stroke and IHD mortality burden; particularly by improving diet and health behaviours at the population level. Our aim is to estimate and compare the potential impact of ischemic stroke treatment vs population level policies on ischemic stroke and IHD deaths in Turkey if achieved like other developed countries up to 2022 and 2032. Methods We developed a Markov model for the Turkish population aged >35 years. The model follows the population over a time horizon of 10 and 20 years. We modelled seven policy scenarios: a baseline scenario, three ischemic stroke treatment improvement scenarios and three population level policy intervention scenarios (based on target reductions in dietary salt, transfat and unsaturated fat intake, smoking prevalence and increases in fruit and vegetable consumption). Parameter uncertainty was explored by including probabilistic sensitivity analysis. Results In the baseline scenario, we forecast that approximately 655, 180 ischemic stroke and IHD deaths (306, 500 in men; 348, 600 in women) may occur in the age group of 35–94 between 2012 and 2022 in Turkey. Feasible interventions in population level policies might prevent approximately 108, 000 (62, 580–326, 700) fewer stroke and IHD deaths. This could result in approximately a 17 % reduction in total stroke and IHD deaths in 2022. Approximately 32 %, 29 %, 11 % and 6 % of that figure could be attributed to a decreased consumption of transfat, dietary salt, saturated fats and fall in smoking prevalence and 22 % could be attributed to increased fruit and vegetable consumption. Feasible improvements in ischemic stroke treatment could prevent approximately 9 % fewer ischemic stroke and IHD deaths by 2022. Conclusions Our modeling study suggests that effective and evidence-based food policies at the population level could massively contribute to reduction in ischemic stroke and IHD mortality in a decade and deliver bigger gains compared to healthcare based interventions for primary and secondary prevention.